Bracovirus Sneaks Into Apoptotic Bodies Transmitting Immunosuppressive Signaling Driven by Integration-Mediated eIF5A Hypusination - Zhou, Gui-Fang; Chen, Chang-Xu; Cai, Qiu-Chen; Yan, Xiang; Peng, Nan-Nan; Li, Xing-Cheng; Cui, Ji-Hui; Han, Yun-Feng; Zhang, Qi; Meng, Jiang-Hui; Tang, Hong-Mei; Cai, Chen-hui; et al. (Frontiers in Immunology, 2022)
A typical characteristic of polydnavirus (PDV) infection is persistent immunosuppression, governed by the viral integration and expression of virulence genes. Recently, activation of caspase-3 by Microplitis bicoloratus bracovirus (MbBV) to cleave Innexins, gap junction proteins, has been highlighted, further promoting apoptotic cell disassembly and apoptotic body (AB) formation. However, whether ABs play a role in immune suppression remains to be determined. Herein, we show that ABs transmitted immunosuppressive signaling, causing recipient cell apoptosis and dismigration. Furthermore, the insertion of viral–host integrated motif sites damaged the host genome, stimulating eIF5A nucleocytoplasmic transport and activating the eIF5A-hypusination translation pathway. This pathway specifically translates apoptosis-related host proteins, such as P53, CypA, CypD, and CypJ, to drive cellular apoptosis owing to broken dsDNA. Furthermore, translated viral proteins, such Vank86, 92, and 101, known to complex with transcription factor Dip3, positively regulated DHYS and DOHH transcription maintaining the activation of the eIF5A-hypusination. Mechanistically, MbBV-mediated extracellular vesicles contained inserted viral fragments that re-integrated into recipients, potentially via the homologous recombinant repair system. Meanwhile, this stimulation regulated activated caspase-3 levels via pI3K/AKT 308 and 473 dephosphorylation to promote apoptosis of granulocyte-like recipients Sf9 cell; maintaining pI3K/AKT 473 phosphorylation and 308 dephosphorylation inhibited caspase-3 activation leading to dismigration of plasmacyte-like recipient High Five cells. Together, our results suggest that integration-mediated eIF5A hypusination drives extracellular vesicles for continuous immunosuppression.